The expression level of fibroblast growth factor gene in serum samples of lung cancer patients: Fibroblast growth factor gene and lung cancer - Bu, Su; Zhang, Wensheng; Chen, Xiaofen; Liu, Li; Pang, Feng; Zhou, Lei (Cellular and Molecular Biology, 2023)
Lung cancer, one of the most deadly and dangerous types of cancer in the world, kills many men and women every year. Activation of fibroblast growth factor signals plays a role in the pathogenesis of several cancers, including lung cancer. Also, this factor may indicate prognosis and is related to the survival rate in patients with NSCLC. Therefore, this research investigated the level of fibroblast growth factor gene expression in the serum of people with lung cancer. In this research, 60 serum samples of healthy people and 60 serum samples of people with NSCLC were prepared, and personal and clinicopathological information of the studied people were collected by questionnaires. Then, plasma isolation, RNA extraction, cDNA synthesis, primers design, implementation, and changes in fibroblast growth factor gene expression in the serum of healthy and lung cancer patients were evaluated by the Real-time PCR method. REST software was used to analyze the results. The findings showed no significant difference in the expression of the fibroblast growth factor gene in the serum of people with the first to third stages of metastasis. However, in the serum of patients with the fourth stage of metastasis, the expression level of this gene was significantly decreased by 3.92 times compared to normal samples (P<0.05). According to the results of this study, it is possible to use the expression level of the fibroblast growth factor gene in people's serum to predict the metastasis stage of lung cancer.